Constitution-making under UN auspices : fostering dependency in sovereign lands - Sripati, Vijayashri (New Delhi : Oxford University Press, 2020)
Post 1960, all colonies enjoyed the right to sculpt their own constitutions without international assistance. Yet, from 1960-2018, over poor 40 sovereign states have adopted with United Nations Constitutional Assistance (UNCA) the Western liberal constitution. Why? A comprehensive study on UNCA, this book shows that based on the UN's official statements, UNCA works ostensibly to 'modernise' poor states. However, this results in an investor-friendly environment that largely benefits powerful transnational interests, only to secure debt-relief. Thus, political control that they experienced when they were colonies, continues in this post-colonial era.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 30, 2020).
Keywords: United Nations; Constitutional history; Constitutional law; Law; Laws of specific jurisdictions & specific areas of law